2003
DOI: 10.1046/j.1365-2141.2003.04522.x
|View full text |Cite
|
Sign up to set email alerts
|

Early reconstitution of the T‐cell repertoire after non‐myeloablative peripheral blood stem cell transplantation is from post‐thymic T‐cell expansion and is unaffected by graft‐versus‐host disease or mixed chimaerism

Abstract: Summary. To study immune recovery after non-myeloablative, reduced-intensity stem cell allografts (NST) and T-cell-depleted myeloablative transplants (TCD), we measured T-cell subset recovery by flow cytometry, T-cell repertoire by spectratyping and thymic T-cell output using a T-cell receptor excision circle (TREC) assay. We found a rapid and comparable increase in lymphocyte numbers in both NST and TCD, supporting the presence of a powerful drive for lymphocyte recovery after transplant. Spectratyping on d 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 47 publications
2
26
0
Order By: Relevance
“…[41][42][43] Although previous investigations suggested poor T cell reconstitution due to thymic injury by GvHD, 44 recently published data showed no differences in T cell subset counts and TREC levels in dependence of GvHD. 45 This is in line with our observations, where we found no significant differences in T cell reconstitution with respect to incidence and extent of GvHD. B lymphocyte recovery returned to normal 1 year after HSCT and was delayed in case of steroids as a part of GvHD prophylaxis, but not influenced by the occurrence of GvHD or following immunosuppression with the use of steroids after HSCT.…”
Section: Discussionsupporting
confidence: 82%
“…[41][42][43] Although previous investigations suggested poor T cell reconstitution due to thymic injury by GvHD, 44 recently published data showed no differences in T cell subset counts and TREC levels in dependence of GvHD. 45 This is in line with our observations, where we found no significant differences in T cell reconstitution with respect to incidence and extent of GvHD. B lymphocyte recovery returned to normal 1 year after HSCT and was delayed in case of steroids as a part of GvHD prophylaxis, but not influenced by the occurrence of GvHD or following immunosuppression with the use of steroids after HSCT.…”
Section: Discussionsupporting
confidence: 82%
“…It is possible that the reduction of median TREC levels observed between M þ 7.5 and M þ 11 could be due to the low number of patients, but we can also hypothesize that this reduction may result either from activation-induced cell death of naı¨ve cells or, more probably, from dilution of the TRECpositive cells, through peripheral naı¨ve T-cell division. 31 This result is in line with data from Bahceci et al, 32 who observed a progressive decrease of TREC contents from day 14 to day 180 after RIC-PBSCT and concluded that early reconstitution resulted from post-thymic T-cell expansion. Our data further suggest that recent thymic emigrants may enter a peripheral expansion that would be added to the initial peripheral expansion of infused T cells.…”
Section: Discussionsupporting
confidence: 82%
“…41 It has been suggested that the more rapid recovery of T cells after RIC-SCT could be the result of peripheral expansion of infused T cells instead of an actual preservation of thymic function. Bahceci et al 32 observed that naïve CD4 þ T-cell numbers were significantly higher in RIC-SCT patients at all time points other than 1 year after transplant in comparison with T-cell depleted MAC-SCT. The levels of TRECs were also significantly higher in RIC recipients than in MAC patients at 45 days after transplant; however, they gradually decreased after the SCT.…”
Section: Thymopoiesis After Ric-sctmentioning
confidence: 99%
“…25,31,32 Taken together, these qualitative differences might lead to faster development of effective immune response against infectious agents and residual host malignant cells.…”
Section: Spotlightmentioning
confidence: 99%